KAJIAN PENANGGULANGAN LIMPASAN PERMUKAAN DENGAN MENGGUNAKAN SUMUR RESAPAN (STUDI KASUS DI DI DAERAH PERUMNAS MADE KABUPATEN LAMONGAN) - Saleh, Chairil (Media Teknik Sipil, 2011)
Desa Donowarih memiliki manajemen penanganan sampah yang buruk, maka perencanaanTPPopulation growth and rapid development led to changes in land use functions. Lots of landwhich was originally in the form of open land or forest to residential and industrial area. It is notonly urban region, but has been extended in the cultivation and protected areas, which serve awater. The impact of land use change surface runoff is rising at the same time decresing infiltrationof water into the ground. As a result the area occurs the reduced flood and infiltration into theground as ground water augmentation. The same thing happened in the Perumnas Made frequentduring the rainy season puddles. To prevent this and also to maintain the required reserves ofground water wells.This study aims to reduce runoff and prevent surface runoff and can increase the potential forground water. Besides, in order to take advantage of rainwater into the ground through wells. Sothat treatment can conserve and save water resources for long-term soil.Building design of water infiltration in this study is the recharge wells. Wells can accommodatesurface runoff and rain fall on every house gutters. Recharge wells in this study is planned in eachhome. Analysis results obtained from the total volume of rainfall with a 2-year return period is =2627.468 m3 while total volume of well is 3022.5 m3. As in every home is planned the wells withcircle radius from 0.45 to 0.75 meters with a variation to the depths of the wells ranged from 1.6 m- 2.9 m. So the wells is very effective to hold the entire discharge with a 2-year return period.Key words: Pond, Recharge Wells